Rhinoviruses: molecular diversity and clinical characteristics - Donia Bouzid; Oshra Hadad; Mélanie Bertine; Nadhira Houhou-Fidouh; Audrey Mirand; Xavier Duval; Vincent Bunel; Raphael Borie; Jean Christophe Lucet; Diane Descamps; Benoit Visseaux (International Journal of Infectious Diseases, 2022)
Background: Rhinoviruses are commonly considered simple “common cold” agents. The link between their molecular epidemiology and patient clinical presentation and outcomes remains unclear in adult populations. Materials/methods: All nasopharyngeal or bronchoalveolar lavages were screened using multiplex PCR in 3 Parisian hospitals from January 2018 to September 2018. For all detected rhinoviruses, the VP2/VP4 region was subtyped by sequencing. Results: The study included 178 unique patients who were positive for human rhinovirus (HRV). They were primarily men (56%), with a median age of 62.2 years (IQR: 46.8–71.4), frequently presenting chronic respiratory diseases (56%) and/or immunosuppression (46%). Of these, 63% were admitted for respiratory distress, including 25% for pneumonia; 95 (53%), 27 (15%), and 56 (32%) were positive for HRV-A, -B, and -C, respectively. HRV-B appeared to be more associated with immunosuppressive treatments (58% vs 30% and 36% of patients for HRV-A and -C, respectively, p = 0.038), higher coinfection rates (54% vs 34% and 23%, p = 0.03), and higher intensive care unit (ICU) admission rates (35% vs 17% and 13%, p = 0.048). Conversely, HRV-A was more frequently associated with pneumonia (54% vs 31% and 11% for HRV-B and -C, respectively, p = 0.01). Conclusions: This study highlights the high proportion of chronic respiratory diseases or immunosuppression among hospitalized patients infected with a rhinovirus. Important: Human rhinoviruses (HRVs) are frequently detected in patients hospitalized for respiratory distress. Understanding their molecular differences is crucial to finding target treatments and improving patient outcomes.